High-strength and high-toughness concrete as well as preparation method and toughness evaluation model thereof

By curing the shape memory polymer on the fiber surface and performing prestress programming, the problem of insufficient compatibility between the fiber and concrete interface is solved, and the strength and toughness of the concrete are significantly improved.

CN119504225AActive Publication Date: 2025-02-25NANJING HYDRAULIC RES INST
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411707676.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-25
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

In the existing mixed fiber concrete preparation process, the interface compatibility between the fiber and the concrete matrix material is poor, resulting in insufficient enhancement and toughening effects.

Method used

Prestressed fibers with shape memory polymers are used to cure surfaces, and a uniform coating of 50-100μm thick is formed on the fiber surface through spraying technology, and shape memory programming is performed to ensure that the fiber retains prestress during cooling.

Benefits of technology

Effectively improve the interface compatibility between fiber and concrete, improve the compressive strength and bending toughness of concrete, and enhance its overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504225A_ABST
    Figure CN119504225A_ABST
Patent Text Reader

Abstract

The invention discloses high-strength and high-toughness concrete, which is prepared from the following components in parts by mass: 300 to 500 parts of coal ash, 300 to 500 parts of slag, 200 to 300 parts of silica fume, 100 to 200 parts of sodium hydroxide solution, 200 to 250 parts of sodium silicate solution, 300 to 400 parts of fine aggregate, 150 to 200 parts of water and prestressed fiber with the volume fraction of 0.5 to 2.0 percent, shape memory polymers are cured on the surfaces of the prestressed fibers. The invention also provides a preparation method of the high-strength and high-toughness concrete and a toughness evaluation model. The high-strength and high-toughness concrete provided by the invention can effectively improve the reinforcing and toughening effects of fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of concrete materials, and in particular to a high-strength and high-toughness concrete and a preparation method and a toughness evaluation model thereof. Background Art

[0002] Nowadays, the building materials used in hydraulic structures are still mainly concrete. Traditional concrete has outstanding advantages such as wide material sources and high economy, but it has many inherent defects when used in infrastructure construction, such as poor tensile properties, high brittleness, insufficient toughness, and difficult to control cracks. In harsh service environments, the insufficient strength (compression, bending, shear) of structural load-bearing components, especially insufficient toughness and failure of node connections, are the main reasons for the damage of hydraulic concrete structures and even the overall failure of the structure. Once a hydraulic structure is damaged, it will seriously threaten the normal use of hydraulic structures, and in severe cases will cause incalculable losses and consequences. Therefore, it is necessary to develop high-performance concrete materials, optimize the strength and toughness of concrete in key parts of hydraulic structures that are easily damaged under harsh service environments, and improve the overall disaster prevention, mitigation and resistance capabilities of hydraulic structures.

[0003] In order to improve the inherent defects of traditional concrete and enhance its strength and toughness, researchers have adopted the method of incorporating chopped fibers into the concrete matrix material to effectively play the bridging role of the fibers to develop high-performance concrete. In the process of high-performance concrete development, two types of concrete materials have received widespread attention. The first is engineering / strain-hardening cementitious composites (ECC) with polymer fibers as the main reinforcement material. This is a high-performance fiber-reinforced composite designed based on micromechanical principles, which can achieve significant strain hardening and multi-crack cracking behavior under direct tension. It is generally reported that the tensile strain capacity of ECC is 1% to 8% (i.e., 100 to 800 times that of ordinary concrete), but its compressive strength is usually below 60 MPa. The second is ultra-high performance concrete (UHPC) with steel fibers as the main reinforcement material. Compared with ordinary ECC materials, UHPC has much higher strength (usually above 60 MPa), but its tensile strain capacity is relatively insufficient (usually less than 1.0%), which seriously limits its application range in actual engineering. In recent years, in order to meet the growing requirements of hydraulic structures such as ports, docks, and dams for the strength and toughness of concrete materials, the research on high-strength and high-toughness concrete has gradually become one of the main development directions of concrete materials.

[0004] In the process of high-performance development of concrete, fiber modification is its core. At the same time, in order to integrate the characteristics of different types of fibers (steel fibers, polymer fibers) to strengthen or toughen concrete matrix materials, the research on hybrid fiber concrete has received widespread attention. For example, the invention patent CN109369095A fully utilizes the performance characteristics of different types and proposes a hybrid fiber concrete and its preparation method and application. However, due to the mismatch of physical and chemical properties, the interface compatibility between fiber and concrete is not good. If the interface compatibility is not good, it may cause the bonding performance between the fiber and the matrix to weaken, the fiber is easy to be pulled out of the matrix, and the excellent tensile properties of the fiber itself cannot be fully utilized. It is difficult to disperse the stress transmitted by the concrete matrix material, which ultimately leads to a decrease in the performance of the concrete material. Therefore, improving the interface characteristics between fiber and concrete is the key to improving the strength and toughness of fiber concrete.

[0005] Therefore, it is necessary to optimize the interface effect between the fiber and the concrete matrix in order to address the deficiencies in the existing technology, and then develop a high-strength and high-toughness concrete with both high strength and high toughness properties, and establish a corresponding flexural toughness evaluation method. Summary of the invention

[0006] Purpose of the invention: In order to solve the problem of poor interface compatibility between fibers and concrete matrix materials in the existing hybrid fiber concrete preparation process, resulting in insufficient reinforcement and toughening effects, the present invention provides a high-strength and high-toughness concrete, a preparation method thereof, and a toughness evaluation model.

[0007] In order to solve the above technical problems, the present invention provides a high-strength and high-toughness concrete, comprising the following components in parts by weight: 300-500 parts of fly ash, 300-500 parts of slag, 200-300 parts of silica fume, 100-200 parts of sodium hydroxide solution, 200-250 parts of sodium silicate solution, 300-400 parts of fine aggregate, 150-200 parts of water and prestressed fibers with a volume fraction of 0.5%-2.0%, wherein the prestressed fibers are fibers with shape memory polymers cured on the surface.

[0008] Specifically, the prestressed fiber is prepared by the following steps: A1: dissolving the shape memory polymer in cyclohexane at a mass ratio of 10%-15%, and mixing well to obtain a shape memory polymer solution; A2. The fiber surface is treated with anhydrous ethanol and plasma in sequence; specifically, the fiber is cleaned with anhydrous ethanol in an ultrasonic cleaner for 10-15 minutes to remove surface grease, dust and other impurities. After that, in order to improve the adhesion of the coating, the fiber surface will be treated with plasma. This step enhances the adhesion effect of the coating by changing the surface energy. A3, spraying the fiber with a shape memory polymer solution using a spraying device, with a coating thickness of 50-100 μm, and then curing to obtain a fiber with a cured coating; A4. The fiber with the cured coating is subjected to shape memory programming. After the shape memory programming is completed, the fiber is naturally cooled to room temperature without removing the tensile force to form a prestressed fiber.

[0009] Shape memory polymers (SMPs) have attracted much attention in the field of materials science due to their unique shape memory effect. When subjected to external stimuli (such as temperature changes), SMPs can transform from one shape to another preset shape. Using this property, prestress can be introduced into concrete materials to cope with complex load conditions and environmental changes.

[0010] When performing the coating preparation step of SMP, it is critical to select the right SMP material. For this application, we chose polyurethane-based SMP, which is particularly suitable for applications that require temperature activation due to its excellent shape memory properties and excellent thermal stability. Polyurethane-based SMP is soft and plastic at ambient temperature, but can quickly harden and remember the new shape when heated to its transition temperature (about 55°C).

[0011] During the preparation of the coating, the polyurethane-based SMP is preferably dissolved in cyclohexane at a mass ratio of 15% to form a uniform solution. The viscosity of the solution is adjusted to be suitable for spraying, and the viscosity should generally be controlled between 1000 and 1200 cP. To ensure the uniformity and functionality of the coating, professional spraying equipment is used. The spraying pressure is set to about 2-3 bar and the nozzle diameter is 0.5 mm, so that a uniform coating of 50-100 μm thickness is formed on the fiber surface. In addition, ensure that the working environment is dust-free to avoid impurities on the coating surface.

[0012] Fiber treatment and coating application are key steps to achieve good interfacial bonding. First, the fiber needs to be thoroughly cleaned to remove surface grease, dust and other impurities, usually using anhydrous ethanol in an ultrasonic cleaner for 15 minutes. After that, to improve the adhesion of the coating, the fiber surface will be plasma treated, a step that enhances the bonding effect of the SMP coating by changing the surface energy.

[0013] The coating is applied by spraying technology because spraying can cover the fiber surface more evenly and ensure the consistency of the coating. During the spraying process, the thickness and uniformity of the coating are controlled to ensure that each fiber is completely and evenly covered.

[0014] The fiber composite includes steel fiber and polymer fiber. The addition ratio of the fiber composite is generally about 0.5%-2.0% of the total volume of concrete, preferably, the addition ratio is 2%, and the ratio of steel fiber to polymer fiber is preferably 1:1-1:3.

[0015] In step A3, the curing condition is: curing the coated fiber at 60-70° C. for 2-3 hours. Preferably, the coated fiber needs to be cured at 60° C. for 2 hours, which is to ensure that the SMP material is completely cured and forms a strong chemical bond with the fiber surface.

[0016] In step A4, the shape memory programming step is as follows: the fiber with the cured coating is placed in a temperature-controlled oven, the temperature is set to 100-120°C, at which temperature, the fiber is mechanically stretched, the strain rate is controlled at 2-3%, and this state is maintained for 30-50 minutes.

[0017] Heat treatment and shape memory programming are the core links to achieve the shape memory effect. Preferably, during the programming stage, the coated fiber is placed in a temperature-controlled oven, and the temperature is set to 100°C, which is higher than the shape fixing temperature of the SMP. At this temperature, the fiber is mechanically stretched, and the strain rate is controlled at 3%, and this state is maintained for 30 minutes. During this process, the SMP material will transform from a temporary form to a fixed stretched state.

[0018] After programming, the fibers are allowed to cool naturally to room temperature without removing the tensile force. This step is critical because it ensures that the fibers do not shrink during cooling and curing, thereby retaining the applied prestress. This prestress will be activated in future applications by a trigger temperature (40-60°C), achieving shape memory recovery of the fibers, thereby introducing prestress in the concrete.

[0019] The average particle size of the fly ash is 8-10 μm; the average particle size of the slag is 8-10 μm; the average particle size of the silica fume is 1-5 μm, and the average particle size of the fine aggregate is 0.5-1.0 mm.

[0020] The concentration of the sodium hydroxide solution is 12-16 M.

[0021] The present invention further proposes a method for preparing the above-mentioned high-strength and high-toughness concrete, comprising the following steps: B1. Weigh 300-500 parts of fly ash, 300-500 parts of slag, 200-300 parts of silica fume and 300-400 parts of fine aggregate components by mass, put them into a mixing device and dry mix for 120-180 seconds; B2. Weigh 100-200 parts of sodium hydroxide solution, 200-250 parts of sodium silicate solution and 150-200 parts of water by mass, pour them into a stirring device at one time, and wet mix for 150-300 s; B3, putting 0.5%-2% by volume of fibers with a shape memory polymer cured on the surface into a stirring device for dry mixing for 120-180 s to evenly distribute the fiber composite to obtain concrete, and finally pouring the evenly mixed fresh mixture into a mold and compacting it by vibration; B4. After curing at room temperature for 20-26 hours, demould the specimen and then transfer it to a standard curing room (controlled temperature at 17-23°C, relative humidity at 90%-95%) for curing until the test age.

[0022] When mixing concrete, the treated fibers are evenly added to the concrete. The fiber addition ratio is generally about 2% of the total volume of the concrete. Use efficient mixing equipment to ensure that the fibers are evenly distributed in the concrete to avoid agglomeration. The uniform distribution of fibers is crucial to achieving the mechanical properties of the overall structure and can effectively enhance the strength and toughness of the concrete.

[0023] Concrete pouring is the final step to achieve structural formation. After the concrete is poured, it is immediately cured to prevent cracks caused by premature drying. During the curing process, special attention is paid to controlling the temperature and humidity conditions (control the temperature at 17-23°C and the relative humidity at 90%-95%). The hydration heat of the concrete will trigger the shape memory effect of the SMP, and the internal temperature of the concrete will rise to 50℃ to 70℃. Maintaining appropriate curing temperature and humidity ensures that the concrete hardens slowly and evenly, while activating the prestress in the SMP fibers.

[0024] This series of steps constitutes a complete program for applying shape memory polymer coating technology to concrete fibers. From material selection and preparation to final application and performance verification, each link is aimed at ultimately achieving the goal of improving the crack resistance and durability of concrete structures.

[0025] The present application further proposes a method for calculating the bending toughness of the above-mentioned high-strength and high-toughness concrete, comprising the following steps: Step 1: Select the concrete component to be tested, conduct a four-point bending test, and draw the load and mid-span deflection test curve of the concrete component to be tested; Step 2: According to the load and mid-span deflection test curve of the concrete member to be tested, obtain the load value P corresponding to the proportional limit point of the concrete member on the test curve. LOP and the mid-span deflection 𝛿 LOP ; At the same time, the load value P corresponding to the rupture modulus point of the concrete component on the test curve is obtained MORand the mid-span deflection 𝛿 MOR ; Step 3: According to the length L of the concrete component to be tested a , width b, height h, clear span L0, proportional limit load P LOP , proportional limit deflection 𝛿 LOP , rupture modulus load P MOR , modulus of rupture deflection 𝛿 MOR , using formulas (1)-(7) to establish the strain hardening bending strength ratio R hm and strain hardening bending energy Q m Calculation method of concrete flexural toughness: Strain hardening flexural strength ratio (1) Strain hardening bending energy (2) Equivalent rupture modulus strength (3) Equivalent proportional ultimate strength (4) Equivalent rupture modulus (5) Equivalent proportional limit energy (6) Pure bending section volume (7) The present invention also proposes the application of the high-strength and high-toughness concrete to the key parts of the drainage structure that are easily damaged.

[0026] Beneficial effects: The high-strength and high-toughness concrete provided by the present invention can effectively improve the reinforcement and toughening effects of fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is the load-deflection curve of Example 1. DETAILED DESCRIPTION

[0028] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments, and the above and / or other advantages of the present invention will become more clear.

[0029] In the following examples, fly ash, slag and silica fume were purchased from Henan Borun Casting Materials Co., Ltd. The average particle size of fly ash is 8-10 μm, and its main chemical components include 30%-40% Al2O3, 45%-55% SiO2, and 1%-5% CaO; the average particle size of slag is 8-10 μm, and its main chemical components include 10%-20% Al2O3, 30%-40% SiO2, and 30%-40% CaO; the sodium hydroxide solution is made of sodium hydroxide flake powder with a purity of 98.5% and a concentration of 14 M; the sodium silicate solution mainly consists of 8.35% Na2O, 26.54% SiO2 and 65.11% H2O; the average particle size of silica ash is 1-5 μm, and its main chemical components include 95%-98% SiO2; the maximum particle size of fine aggregate is 1 mm, and the average particle size is 0.645 mm; the mixed fiber is composed of steel fiber and polymer fiber, and the volume fraction of the two in the total raw materials is 0.5%-2.0%.

[0030] Example 1 A high-strength and high-toughness concrete is prepared by the following steps: (1) Preparation of prestressed fibers: The fibers used in this application include steel fibers and polymer fibers, wherein the steel fibers are copper-plated steel fibers produced by Hebei Biaocai Rubber Products Co., Ltd., with a length of 13 mm, a diameter of 0.20 mm, and a density of 7.80 g / cm 3 , tensile strength 2930 MPa, elastic modulus 210 GPa; polymer fiber is PE fiber produced by Hubei Jiateng Textile Co., Ltd., with a length of 13 mm, a diameter of 0.025 mm, and a density of 0.97 g / cm 3 , tensile strength 3100 MPa, elastic modulus 122 GPa.

[0031] The above two fibers are prepared into prestressed rigid fibers and prestressed polymer fibers respectively by the following steps: A1. Dissolving a polyurethane-based shape memory polymer (SMP) in cyclohexane at a mass ratio of 15% to form a uniform solution; A2. Clean the fiber in an ultrasonic cleaner with anhydrous ethanol for 15 minutes to remove surface grease, dust and other impurities. Then, in order to improve the adhesion of the SMP coating, the fiber surface will be plasma treated. This step enhances the bonding effect of the SMP coating by changing the surface energy. A3. Use a spraying device to spray the fiber so that the SMP coating adheres to the fiber surface. The spraying pressure is set to about 2-3 bar and the nozzle diameter is 0.5 mm, so as to form a uniform coating of 50-100 μm thick on the fiber surface. The fiber after the coating needs to be cured at 60°C for 2 hours to ensure that the SMP material is fully cured and forms a strengthened chemical bond with the fiber surface. A4. The fiber with cured coating is placed in a temperature-controlled oven, and the temperature is set to 100°C, which is higher than the shape fixing temperature of SMP. At this temperature, the fiber is mechanically stretched, and the strain rate is controlled at 2-3%, and maintained in this state for 30 minutes. In this process, the SMP material will transform from a temporary form to a fixed stretched state.

[0032] A5. After shape memory programming is completed, the fiber is naturally cooled to room temperature without removing the tensile force. The fiber will not shrink during the cooling and solidification process, thereby retaining the applied prestress to form a prestressed fiber.

[0033] (2) Preparation method of high-strength and high-toughness concrete.

[0034] Take 520 parts of fly ash, 520 parts of slag, 260 parts of silica fume, and 390 parts of fine aggregate by mass and dry mix them for 150 s; then add 156 parts of sodium hydroxide solution, 234 parts of sodium silicate solution, and 182 parts of water by mass and wet mix them for 300 s. Finally, add 2.0% prestressed fiber (composed of 0.5% prestressed steel fiber and 1.5% prestressed polymer fiber) by volume fraction and dry mix for 150 s to make the fiber composite evenly distributed to obtain concrete. Finally, pour the evenly mixed fresh mixture into a mold and make it dense by vibration. After standing and curing at room temperature for 20-26 hours, demould the sample and then transfer it to a standard curing room (control the temperature at 17-23°C and the relative humidity at 90%-95%) for curing until the test age.

[0035] Example 2 The basic formula and preparation process are the same as those of Example 1, except that the final volume fraction of 2.0% prestressed fiber mixed ratio is different (composed of 1.0% prestressed steel fiber and 1.0% prestressed polymer fiber).

[0036] Comparative Example 1 The basic formula and preparation process are the same as those in Example 1, except that the final volume fraction of 2.0% prestressed fiber mixed ratio is different (consisting of only 2.0% prestressed polymer fibers).

[0037] Comparative Example 2 The basic formula and preparation process are the same as those of Example 1, except that the final volume fraction of 2.0% prestressed fiber mixed ratio is different (composed of 1.5% prestressed steel fiber and 0.5% prestressed polymer fiber).

[0038] Comparative Example 3 The basic formula and preparation process are the same as those of Example 1, except that the final volume fraction of 2.0% prestressed fiber mixed ratio is different (consisting of only 2.0% prestressed steel fiber).

[0039] Comparative Example 4 The basic formula and preparation process are the same as those in Example 1, except that the same amount of hybrid fibers input have no prestressed coating, that is, 0.5% of steel fibers and 1.5% of polymer fibers are directly added.

[0040] Comparative Example 5 The basic formula and preparation process are the same as those in Example 1, except that no fiber is added to the matrix, that is, the matrix is ​​pure matrix material.

[0041] The various properties of the concrete specimens obtained from the examples and comparative examples after standard curing were tested: (1) For 50×50×50 mm 3 The uniaxial compression performance test was carried out on the cubic specimens to determine the compressive strength of the specimens of each embodiment and comparative example. The test was carried out in accordance with the "Concrete Physical and Mechanical Properties Test Method Standard GB / T50081-2019", and the 3000 kN microcomputer-controlled pressure testing machine produced by Shanghai Hualong Testing Instrument Co., Ltd. was used for the test. According to the test specifications, the loading speed was 0.5 MPa / s, and the test results are shown in Table 1.

[0042] (2) For 400×100×15 mm 3 The thin plate specimens were subjected to four-point bending performance tests to measure the bending performance of the specimens of each embodiment and comparative example. The test was conducted in accordance with the "Concrete Physical and Mechanical Properties Test Method Standard GB / T50081-2019" and was measured using a 2000 kN electro-hydraulic servo universal testing machine produced by Shanghai Hualong Testing Instrument Co., Ltd. According to the test specifications, the loading speed was 0.5 mm / min, and the calculation results of the relevant characteristic parameters are shown in Table 2-4.

[0043] The calculation method of the flexural toughness of concrete is as follows: Step 1: Select the concrete component to be tested, conduct a four-point bending test, and draw the load and mid-span deflection test curve of the concrete component to be tested; Step 2: According to the load and mid-span deflection test curve of the concrete member to be tested, obtain the load value P corresponding to the proportional limit point of the concrete member on the test curve. LOPand the mid-span deflection 𝛿 LOP ; At the same time, the load value P corresponding to the rupture modulus point of the concrete component on the test curve is obtained MOR and the mid-span deflection 𝛿 MOR .

[0044] Step 3: According to the length L of the concrete component to be tested a , width b, height h, clear span L0, proportional limit load P LOP , proportional limit deflection 𝛿 LOP , rupture modulus load P MOR , modulus of rupture deflection 𝛿 MOR , establish the bending strength ratio R including strain hardening hm and strain hardening bending energy Q m Calculation method of concrete flexural toughness.

[0045] The calculation method of concrete bending toughness is as follows: Strain hardening flexural strength ratio (1) Strain hardening bending energy (2) Equivalent rupture modulus strength (3) Equivalent proportional ultimate strength (4) Equivalent rupture modulus (5) Equivalent proportional limit energy (6) Pure bending section volume (7) Table 1 Compressive strength test results of examples and comparative examples Table 2 Characteristic parameters of load-deflection curves of examples and comparative examples Table 3 Calculation results of bending characteristic parameters of the embodiments and comparative examples Table 4 Calculation results of bending toughness parameters of examples and comparative examples Based on the above characteristic parameters, it can be known that the application of the high-strength and high-toughness concrete provided by the present invention can effectively improve the reinforcement and toughening effects of the fiber, and the calculated value of the bending toughness characteristic parameter of the embodiment is better than that of the comparative example.

[0046] The present invention provides a concept and method for high-strength and high-toughness concrete. There are many methods and ways to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A high-strength and high-toughness concrete, characterized in that: The invention comprises the following components in parts by mass: 300-500 parts of fly ash, 300-500 parts of slag, 200-300 parts of silica fume, 100-200 parts of sodium hydroxide solution, 200-250 parts of sodium silicate solution, 300-400 parts of fine aggregate, 150-200 parts of water and prestressed fiber with a volume fraction of 0.5%-2.0%, wherein the prestressed fiber is a fiber composite with a shape memory polymer cured on the surface, and the shape memory polymer is a polyurethane-based shape memory polymer or a copolyamide-based shape memory polymer.

2. The high-strength and high-toughness concrete according to claim 1, characterized in that: The prestressed fiber is prepared by the following steps: A1: dissolving the shape memory polymer in cyclohexane at a mass ratio of 10%-15%, and mixing well to obtain a shape memory polymer solution; A2, treating the fiber surface with anhydrous ethanol and plasma in turn; A3, spraying the fiber with a shape memory polymer solution using a spraying device, with a coating thickness of 50-100 μm, and then curing to obtain a fiber with a cured coating; A4. The fiber with the cured coating is subjected to shape memory programming. After the shape memory programming is completed, the fiber is naturally cooled to room temperature without removing the tensile force to form a prestressed fiber.

3. The high-strength and high-toughness concrete according to claim 2, characterized in that: In A2, the fibers include steel fibers and polymer fibers.

4. The high-strength and high-toughness concrete according to claim 2, characterized in that: In step A3, the curing conditions are: curing the coated fiber at 60-70° C. for 2-3 hours.

5. The high-strength and high-toughness concrete according to claim 2, characterized in that: In step A4, the shape memory programming step is as follows: the fiber with the cured coating is placed in a temperature-controlled oven, the temperature is set to 100-120°C, at which temperature, the fiber is mechanically stretched, the strain rate is controlled at 2-3%, and this state is maintained for 30-50 minutes.

6. The high-strength and high-toughness concrete according to claim 1, characterized in that: The average particle size of the fly ash is 8-10 μm; the average particle size of the slag is 8-10 μm; the average particle size of the silica fume is 1-5 μm; the average particle size of the fine aggregate is 0.5-1.0 mm; and the concentration of the sodium hydroxide solution is 12-16 M.

7. The method for preparing the high-strength and high-toughness concrete according to any one of claims 1 to 6, characterized in that: The steps include: B1. Weigh 300-500 parts of fly ash, 300-500 parts of slag, 200-300 parts of silica fume and 300-400 parts of fine aggregate components by mass, put them into a mixing device and dry mix for 120-180 seconds; B2. Weigh 100-200 parts of sodium hydroxide solution, 200-250 parts of sodium silicate solution and 150-200 parts of water by mass, pour them into a stirring device at one time, and wet mix for 150-300 s; B3, putting 0.5%-2% by volume of fibers with a shape memory polymer cured on the surface into a stirring device for dry mixing for 120-180 s to evenly distribute the fibers to obtain concrete, and finally pouring the evenly mixed new mixture into a mold and compacting it by vibration; B4. After standing and curing at room temperature for 20-26 hours, the specimen is demoulded and then transferred to a standard curing room for curing until the test age.

8. The preparation method according to claim 7, characterized in that: The curing conditions are: control the temperature at 17-23℃ and the relative humidity at 90%-95%.

9. The method for calculating the bending toughness of high-strength and high-toughness concrete according to any one of claims 1 to 6, characterized in that: The steps include: Step 1: Select the concrete component to be tested, conduct a four-point bending test, and draw the load and mid-span deflection test curve of the concrete component to be tested; Step 2: According to the load and mid-span deflection test curve of the concrete member to be tested, obtain the load value P corresponding to the proportional limit point of the concrete member on the test curve. LOP and the mid-span deflection 𝛿 LOP ; At the same time, the load value P corresponding to the rupture modulus point of the concrete component on the test curve is obtained MOR and the mid-span deflection 𝛿 MOR ; Step 3: According to the length L of the concrete component to be tested a , width b, height h, clear span L0, proportional limit load P LOP , proportional limit deflection 𝛿 LOP , rupture modulus load P MOR , modulus of rupture deflection 𝛿 MOR , using formulas (1)-(7) to establish the strain hardening bending strength ratio R hm and strain hardening bending energy Q m Calculation method of concrete flexural toughness: Strain hardening flexural strength ratio (1) Strain hardening bending energy (2) Equivalent rupture modulus strength (3) Equivalent proportional ultimate strength (4) Equivalent rupture modulus (5) Equivalent proportional limit energy (6) Pure bending section volume (7).

10. Use of the high-strength and high-toughness concrete according to any one of claims 1 to 6 in key parts of drainage structures that are easily damaged.

Citation Information

Patent Citations

  • Hybrid fiber reinforced concrete, and preparation method and application thereof

    CN109369095A

  • High-strength ultra-high-toughness concrete and preparation method thereof

    CN105948660A

  • Preparation method of shape memory polyurethane based composite material type cement road surface joint sealing material

    CN107513146A

  • High-toughness concrete raw material selection method

    CN109796167A

  • Oxidation-induced shape memory fiber as well as preparation method and application thereof

    CN111196733A